An Anterior Cruciate Ligament Rupture Increases Levels of Urine N-terminal Cross-linked Telopeptide of Type I Collagen, Urine C-terminal Cross-linked Telopeptide of Type II Collagen, Serum Aggrecan ARGS Neoepitope, and Serum Tumor Necrosis Factor–α. Issue 13 (November 2021) - Hagemans, Frans J.A.; Larsson, Staffan; Reijman, Max; Frobell, Richard B.; Struglics, Andre; Meuffels, Duncan E.
Background: An anterior cruciate ligament (ACL) rupture results in an increased risk of developing knee osteoarthritis (OA) at an early age. Before clinical signs become apparent, the OA process has already been initiated. Therefore, it is important to look at the cascade of changes, such as the activity of cytokines and proteases, which might be associated with the later development of OA. Purpose: To compare biomarker levels in patients with a recent ACL rupture with those in controls with a healthy knee and to monitor biomarker levels over 2 years after an ACL rupture. Study Design: Descriptive laboratory study. Methods: Patients were enrolled after an ACL tear was identified. Serum and urine samples were collected at the time of enrollment in the study (3-25 weeks after the injury) and then at 14 and 27 months after the injury between January 2009 and November 2010. Reference samples were obtained from participants with healthy knees. The following biomarkers were measured with immunological assays: aggrecan ARGS neoepitope (ARGS-aggrecan), tumor necrosis factor–α (TNF-α), interferon-γ, interleukin (IL)–8, IL-10, IL-13, N-terminal cross-linked telopeptide of type I collagen (NTX-I), and C-terminal cross-linked telopeptide of type II collagen (CTX-II). Results: Samples were collected from 152 patients with an acute ACL rupture, who had a median age of 25 years (interquartile range [IQR], 21-32 years). There were 62 urine reference samples (median age, 25 years [IQR, 22-36 years]) and 26 serum reference samples (median age, 35 years [IQR, 24-39 years]). At a median of 11 weeks (IQR, 7-17 weeks) after trauma, serum levels of both ARGS-aggrecan and TNF-α were elevated 1.5-fold ( P < .001) compared with reference samples and showed a time-dependent decrease during follow-up. Urine NTX-I and CTX-II concentrations were elevated in an early phase after trauma (1.3-fold [ P < .001] and 3.7-fold [ P < .001], respectively) compared with reference samples, and CTX-II levels remained elevated compared with reference samples at 2-year follow-up. Strong correlations were found between serum ARGS-aggrecan, urinary NTX-I, and urinary CTX-II ( r s = 0.57-0.68). Conclusion: In the first few months after an ACL injury, there was a measurable increase in serum levels of ARGS-aggrecan and TNF-α as well as urine levels of NTX-I and CTX-II. These markers remained high compared with those of controls with healthy knees at 2-year follow-up.